Processos de construção da autoria nas provas do ENEM - Jesus, Joseilda Martins de (2017)
Being important to study about the way the authorship is constructed, considering the observation about how motivator texts works onto the wording’s texture, it is proposed, theoretically based on Pêcheux’s Discourse Analyses, to analyze the process by which the candidate-subjects become authors on the tests of Exame Nacional do Ensino Médio (ENEM), important selection mechanism for, among other functions, to gain access into public as well as private college education. Therefore, the objective is to verify if there is an authorship’s production control from the motivator texts which are characterized as texts that present a set of information related to the theme proposed, serving as guides so that the candidate-subject elaborates the text. Thus, it is intended to discuss the constitution of the author-subject on theses exams and verify if, and how, the motivator texts direct the authorship’s process. In order to develop this research it is used as corpora the wording proposals of ENEM, in 2011 and 2014, as well as four texts with 1000 grade, which, presented the best requirements related to the evaluation parameters. As a result, it was observed that linguistic marks of the wording proposal and motivator texts reading that compound the writing task, worked as an authoritarian discourse, since they make the candidates deny other interpretation which might not agree with the motivator texts. There was not a movement of total disagreement with the Discourse Formation of the motivator texts, but disassociation attempts, which did not happen completely, since the candidates used the senses generated from them. On this way, the discourse of the wording proposal silenced the candidates, producing an interdiction and censorship discourse of the possible senses which might be generated by them, installing the local silence (ORLANDI, 1997) limiting the authorship’s position of the candidates on the wordings.